A CASE SERIES OF THREE CHINESE-MALAYSIAN PATIENTS WITH VARIED CHARACTERISTICS OF LATENT AUTOIMMUNE DIABETES IN ADULT (LADA) - Azhari, Muhammad Aiman Mohd; Daud, Mas Suria Mat; Amin, Md Syazwan Md (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Latent autoimmune diabetes in adults (LADA) is an autoimmune diabetes typically present in adulthood with initial insulin independence and positive anti-glutamic acid decarboxylase (GAD) antibodies. Most progress to insulin dependence within six months of diagnosis. We present three Chinese-Malaysian patients with LADA, each demonstrating varied presentations and management, all culminating in diabetic complications. CASE Case 1. A 53-year-old lean male with a 22-year history of presumed Type 2 Diabetes Mellitus (T2DM), initially managed with oral agents for ten years and later transitioned to premixed insulin, presented with recurrent diabetic ketoacidosis (DKA). His first DKA was at 51 and subsequently required titration of insulin therapy during follow-up. Two years later, he experienced another DKA episode. Autoimmune testing revealed high-titer anti-GAD antibodies, confirming LADA. Case 2. A 68-year-old male with a 15-year history of presumed T2DM presented with recurrent DKA following insulin interruption and initiation of an SGLT2 inhibitor. Initially managed with two oral agents, he experienced progressive glycemic deterioration after eight years, necessitating insulin therapy. He was positive for anti-GAD antibodies, confirming the diagnosis of LADA. Case 3. A 71-year-old female with a three-year history of presumed T2DM was initiated on premixed insulin alongside oral agents due to poor glycemic control. Despite this, she experienced recurrent DKA, triggered by brief interruptions in insulin therapy. This raised suspicion for LADA despite her advanced age. Autoantibody was positive for anti-GAD antibodies, confirming the diagnosis. CONCLUSION These cases highlight the variable and delayed presentation of LADA, which is frequently misclassified as T2DM. A higher rate of LADA is observed amongst the ethnic Chinese population in Malaysia, mirroring the high prevalence amongst T2DM patients in China. Features such as early treatment failure, recurrent DKA and insulin sensitivity in Chinese ethnicity should raise clinical suspicion, as timely antibody testing is crucial for accurate diagnosis and management.